Storytelling as a Pedagogy to Scaffold Critical Thinking Skills: A Thematic Review - Shrestha, Parshu Ram (Journal of NELTA Koshi (JoNK), 2024)
Storytelling is a scantily discussed teaching method in Nepal. Though mentioned in the school curricula, the situation of research and practices in storytelling as a method used in English language classrooms is not clear. To understand storytelling’s effectiveness as a teaching method, and its connection with critical thinking skills, it is important to ask how it has been perceived and explored by the teachers and researchers respectively. This study was conducted with 25 research articles (out of total 90 articles downloaded from different Internet sources) published in the field. This study has concluded with the results that show storytelling can be a good method in English language classrooms to help students enhance their critical thinking skills, and various forms of storytelling with variety of tools and techniques can be used for the purpose.